Activity of granulomatosis with polyangiitis and its correlation with mTOR phosphoproteomics in neutrophils - Marcin Surmiak; Katarzyna Wawrzycka-Adamczyk; Joanna Kosałka-Węgiel; Anna Włudarczyk; Marek Sanak; Jacek Musiał (Frontiers in Immunology, 2023)
IntroductionGranulomatosis with polyangiitis (GPA) is a small vessel vasculitis with a complex pathomechanism. Organ damage in GPA is also mediated by extracellular trap formation (NETosis). We analyzed the functional status of phosphoproteins modulating NETosis in neutrophils by the mammalian target of rapamycin (mTOR) pathway in GPA along with NETosis biomarkers.MethodsPhosphoproteins levels measured in isolated neutrophils from 42 patients with GPA (exacerbation n=21; remission n=21) and 21 healthy controls were compared to serum biomarkers of the disease.ResultsNeutrophils in active disease manifested lowered levels of phosphorylated mTOR(Ser2448), PTEN(Ser380) and ULK1(Ser555), whereas phosphorylated GSK-3α/β(Ser21/Ser9) was elevated. Exacerbation of GPA was characterized by elevated neutrophil dsDNA in serum, circulating mitochondrial DNA, and DNA-MPO complexes. A significant negative correlation between mTOR or PTEN phosphoproteins and biomarkers of GPA activity was also present, reflecting the clinical activity score of GPA. Positive correlations between phosphorylated GSK-3 α/β and circulating mtDNA, DNA-MPO complexes, neutrophil-released dsDNA, or circulating proteins were also significant. Increased serum levels of IGFBP-2, TFF-3, CD147, and CHI3L1 accompanied GPA exacerbation, whereas DPP-IV levels were the lowest in active GPA. Using a principal component analysis basigin, PTEN and mTOR had the highest loadings on the discrimination function, allowing classification between active, remission, and control subjects with 98% performance.ConclusionsWe present evidence that inhibited mTOR signaling accompanies NETosis in patients with GPA. The functional status of phosphoproteins suggests simultaneous activation of NETosis and autophagy. These results give rise to the study of autophagy as a mechanism underlying granuloma formation in GPA.